APAKAH KARAKTERISTIK PERUSAHAAN DAN ATRIBUT AUDIT MEMENGARUHI TAX AVOIDANCE? - Kusumadani, Handika; Deasy Ariyanti Rahayuningsih (Faculty of Economics and Business University of Mataram, 2023)
This study aims to obtain empirical evidence and analyze the factors that influence tax avoidance. The independent variables in this study are profitability, leverage, company size, company age, sales growth, audit committee, and audit quality. The dependent variable in this study is tax avoidance. The objects in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The number of samples that were successfully obtained using the purposive sampling method was 61 companies with a total of 183 data. This study used multiple regression to determine the effect of the independent variables on profitability, leverage, company size, company age, sales growth, audit committee, and audit quality on variables dependent on tax avoidance. The results of this study indicate that profitability has a positive effect on tax avoidance and leverage has a negative effect on tax avoidance while company size, company age, sales growth, audit committee, and audit quality do not affect tax avoidance. The implications for the results of this study focus on improving tax regulations and increasing taxpayer awareness to minimize tax avoidance.